On the physical origin of the nozzle characteristic and its connection with the double-arcing phenomenon in a cutting torch - Prevosto, Leandro (2009)
The nozzle current-voltage characteristic for a cutting arc is presented in this work. The measurements are reported using a high energy density cutting arc torch with a nozzle bore radius of 0.5 mm. The arc current was fixed at 30 A while the plenum pressure and the oxygen gas mass flow rate were varied in the range of 0.55-0.65 MPa and 0.32-0.54 g s-1, respectively. The results show a very low electron density and the lack of electron attachment at the plasma boundary layer. No ion saturation current was found. For the smallest mass flow rate value gas breakdown was found for a biasing nozzle potential close to that of the cathode, but no evidence of such breakdown was found for the larger mass flow rate values. Using an expression for the ion speed at the entry of the collisional sheath formed between the nonequilibrium plasma and the negatively biased nozzle wall together with a generalized Saha equation coupled to the ion branch of the characteristic, the radial profile of the electron temperature, the spatial distribution of the plasma density at the plasma boundary, and the sheath thickness were obtained. In particular, the obtained thickness value at the breakdown condition was in good agreement with that obtained from the oxygen Paschen's curve. An electron temperature of about 4700-5700 K and a corresponding plasma density of the order of 1019 - 1020 m-3 were found close to the nozzle wall. A physical interpretation on the origin of the double-arcing phenomenon is presented, that explains why the double-arcing (that it is established when the sheath breaks down) appears at low values of the gas mass flow. © 2009 American Institute of Physics.